Hole-extraction and photostability enhancement in highly efficient inverted perovskite solar cells through carbon dot-based hybrid material. (August 2019) - Benetti, Daniele; Jokar, Efat; Yu, Che-Hsun; Fathi, Amir; Zhao, Haiguang; Vomiero, Alberto; Wei-Guang Diau, Eric; Rosei, Federico
Abstract: We report the effect of the integration of carbon dots (Cdots) in high-performance inverted planar-heterojunction (PHJ) perovskite solar cells (PSCs). We used Cdots to modify the hole-transport layer in planar PSC devices. By introducing Cdots on graphene oxide (GO) as hole-transporting layer, the efficiency of the PSC improved significantly from 14.7% in the case of bare GO to 16.2% of the best device with optimized Cdots content. When applying Cdots with an engineered absorption in the UV range as downshifting layer, the device performance was further improved, attaining a maximum PCE of 16.8% (+14%); the stability of the device was also enhanced of more than 20%. Kelvin probe force microscopy (KPFM) and cyclic voltammetry (CV) were employed to analyze the electronic band alignment at the interface between GO/Cdots and the perovskite film. Holes were extracted and transferred to the conductive substrate more efficiently in the presence of Cdots, thus delaying charge recombination. Photoluminescence (PL), transient PL decays and transient photovoltage (TPV) decays investigated the charge-transfer kinetics and proved the retardation of charge recombination. This work reveals an effective enhancement of the performance of planar PSCs by using Cdots/GO as hole transport material. Graphical abstract: Image 1 Highlights: Carbon Dots hybrid material is used in place of PEDOT:PSS as hole transporting material. UV-Absorbing Carbon Dots is used as downshifting layer to improve the efficiency and the long term stability of the device. The efficiency improved significantly from 14.7% to 16.8% of the best device with optimized Cdots content. The presence of Cdots on graphene oxide increases the rate of hole injection and decreases charge recombination.